2015
DOI: 10.1175/jas-d-14-0274.1
|View full text |Cite
|
Sign up to set email alerts
|

The Microphysics of Ice and Precipitation Development in Tropical Cumulus Clouds

Abstract: The rapid glaciation of tropical cumulus clouds has been an enigma and has been debated in the literature for over 60 years. Possible mechanisms responsible for the rapid freezing have been postulated, but until now direct evidence has been lacking. Recent high-speed photography of electrostatically suspended supercooled drops in the laboratory has shown that freezing events produce small secondary ice particles. Aircraft observations from the Ice in Clouds Experiment-Tropical (ICE-T), strongly suggest that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
224
1
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(265 citation statements)
references
References 56 publications
21
224
1
2
Order By: Relevance
“…As activation numbers for the individual ice formation schemes are tracked by the model, we will verify this reduction in a subsequent figure and table. The profound loss of liquid mass following initial ice formation at temperatures warmer than -10°C is similar to the rapid glaciation observed in strong 20 updrafts in the study of Lawson et al (2015), which was suggested to occur due to the cascading formation of small crystals from drop freezing ice multiplication processes and subsequent riming.…”
Section: Hydrometeor Concentration and Psd 25supporting
confidence: 69%
See 3 more Smart Citations
“…As activation numbers for the individual ice formation schemes are tracked by the model, we will verify this reduction in a subsequent figure and table. The profound loss of liquid mass following initial ice formation at temperatures warmer than -10°C is similar to the rapid glaciation observed in strong 20 updrafts in the study of Lawson et al (2015), which was suggested to occur due to the cascading formation of small crystals from drop freezing ice multiplication processes and subsequent riming.…”
Section: Hydrometeor Concentration and Psd 25supporting
confidence: 69%
“…While ice multiplication from the Hallett-Mossop scheme is active in both cases, removing the depositional-condensation nucleation is sufficient to reduce graupel formation and delay the glaciation of the clouds until temperatures near the homogeneous freezing level 25 where immersion freezing is most active. The observations/modeling studies of Lawson et al (2015) and Ackerman et al (2015) both suggest that this effect on cloud glaciation can be explained by sufficiently fast ice multiplication at warmer temperatures, creating small ice crystals similar to the effects of significantly large deposition-condensation freezing, although it should be noted that primary ice formation was not the focus of those studies and ice nucleation was treated simply, leaving a possible gap in the understanding of the interactions between the ice nucleation and ice multiplication 30 processes. In our simulation the removal of the deposition-condensation freezing greatly hinders the formation of midlevel ice, despite an unchanged IN concentration and active ice multiplication, showing the importance of even small number of midlevel ice formation to the overall vertical hydrometeor distribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The liquid fraction is correlated to the vertical velocity between −3 and −8 • C, possibly because the Hallet-Mossop process is more significant in weaker updrafts (Heymsfield and Willis, 2014). Lawson et al (2015) show that the existence of millimeter drops in the convective clouds can result in fast ice initiation, and the significant latent heat released during the ice initiation process can strengthen the updrafts. In ICE-T and COPE, we also observe many millimeter drops, which may strongly interact with vertical velocity through a fast ice initiation process.…”
Section: Discussionmentioning
confidence: 90%